2019
DOI: 10.3906/sag-1805-92
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation should be given in breath-holding spells regardless of anemia

Abstract: Background/aim: The purpose of this retrospective study was to determine the effectiveness of oral iron therapy in breath-holding spells and evaluation of electrocardiographical changes. Materials and methods: Three hundred twelve children aged 1-48 months and diagnosed with breath-holding spells between January 2017 and April 2018 were included. Patients' laboratory findings were compared with 100 patients who had one simple febrile seizure. Results: Cyanotic breath-holding spells were diagnosed in 85.3% (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
5
15
1
Order By: Relevance
“…The reported mean age of onset is generally 6-12 months (2,8,9). The reported incidence of a family history of epilepsy has ranged from 7.7 to 29% (10,13,14). In consistence with the previous literature, the same figure was determined to be 19.1% in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The reported mean age of onset is generally 6-12 months (2,8,9). The reported incidence of a family history of epilepsy has ranged from 7.7 to 29% (10,13,14). In consistence with the previous literature, the same figure was determined to be 19.1% in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Data on the genetic predisposition or family history of BHS may vary between countries. Studies from Turkey have reported similar figures (10,11).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our results were in good agreement with other studies. 17,[23][24][25] Abbreviations: Hb, hemoglobin; Hct, hematocrit; MCV, mean corpuscular volume; TIBC, total iron-binding capacity. *P < .001 when compared to the nontreated group.…”
Section: Discussionmentioning
confidence: 99%